2019
DOI: 10.1016/j.cognition.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Understanding facial impressions between and within identities

Abstract: A paradoxical finding from recent studies of face perception is that observers are error-prone and inconsistent when judging the identity of unfamiliar faces, but nevertheless reasonably consistent when judging traits. Our aim is to understand this difference. Using everyday ambient images of faces, we show that visual image statistics can predict observers' consensual impressions of trustworthiness, attractiveness and dominance, which represent key dimensions of evaluation in leading theoretical accounts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 64 publications
4
22
0
Order By: Relevance
“…Recent studies have already demonstrated that the variability in social trait evaluations attributed to different face photographs of the same person is indeed substantial, to the extent that it matches or sometimes even exceeds the variability in social ratings attributed to images of different people (Jenkins et al, 2011; Todorov & Porter, 2014). This pattern of results has been reported for many different social traits, including attractiveness, trustworthiness, dominance, competence, creativity, and others, in both natural and more controlled face stimuli sets (Mileva, Young, et al, 2019; Sutherland et al, 2017). Estimating the relative proportion of within- and between-person variability in social ratings has important implications for the existing literature, which often takes a single (usually highly standardized) image as a veridical representation of a person.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Recent studies have already demonstrated that the variability in social trait evaluations attributed to different face photographs of the same person is indeed substantial, to the extent that it matches or sometimes even exceeds the variability in social ratings attributed to images of different people (Jenkins et al, 2011; Todorov & Porter, 2014). This pattern of results has been reported for many different social traits, including attractiveness, trustworthiness, dominance, competence, creativity, and others, in both natural and more controlled face stimuli sets (Mileva, Young, et al, 2019; Sutherland et al, 2017). Estimating the relative proportion of within- and between-person variability in social ratings has important implications for the existing literature, which often takes a single (usually highly standardized) image as a veridical representation of a person.…”
supporting
confidence: 79%
“…Different groups of participants rated 20 face or voice stimuli of 20 unfamiliar identities (10 female) for trustworthiness, dominance, and attractiveness on a 9-point Likert scale. For the trait ratings of faces, we describe a reanalysis of existing data of social evaluations of faces reported in Mileva, Young, et al (2019, Study 1). Details of the participants recruited and methods used are described again below.…”
Section: Experiments 1: Variability In Trait Ratings Attributed To Fa...mentioning
confidence: 99%
“…One reason why the role of familiarity for interpreting highly changeable signals is small (relative to its prominent role for recognition) seems to be that whilst there are identity-specific differences that can to some extent limit the universality of characteristics that underlie social signals, these are relatively small compared to the identity-specificity of perceptual signals of personal identity [133]. This has the useful consequence of facilitating the many interactions with strangers that characterise much of modern life (or simply watching television).…”
Section: Box 3: Functional Demands Of Identity Recognition and Emotion Recognitionmentioning
confidence: 99%
“…In fact the lines of best fit have identical slopes of 0.20 increase in hit confidence for each step in familiarity. Univariate ANOVA confirms a significant linear trend for both the same image (F(1,129) However, precisely because different pictures look different (Mileva et al, 2019), the new one may not 'look like' Fred in which case there will be no advantage. Since it is unlikely that such competing effects would so exactly cancel out, a simpler explanation may be that, in this context, the same image engages 'face processing' to the same extent as a different image.…”
Section: Resultsmentioning
confidence: 78%